Differences in the immune microenvironment between improved and non-improved cases of vitiligo after halo nevus excision. Issue 3 (March 2023) - Kano, Shinji; Nakamura, Motoki; Nojiri, Yuka; Magara, Tetsuya; Yoshimitsu, Maki; Kato, Hiroshi; Morita, Akimichi
Abstract: Background: Halo nevus, also called Sutton's nevus, is a nevus cell nevus surrounded by vitiligo thought to be caused by a T-cell mediated immune response to the nevus antigen. The immune microenvironment is mysterious, however, as vitiligo often does not improve even when the nevus cells are removed. Objectives: To analyze the clinical course and immune microenvironment of patients with halo nevus who had undergone nevus excision. Methods: We collected 54 halo nevus patients and performed multivariate analysis and immunohistochemical analysis, including multiplexed immune cell phenotyping and spatial single-cell analyses using the PhenoCycler® assay. Results: Multivariate analysis revealed that only the presence or absence of vitiligo vulgaris at the time of consultation was associated with improvement in the surrounding vitiligo following excision. Expression of programmed death-ligand 1 in nevus cells was significantly higher in non-improved cases compared with improved cases. The PhenoCycler® assay revealed that CD107a-positive and CD21-positive cells were more prevalent in improved cases than in non-improved cases. In the improved cases, active cell-cell interactions, centered on CD21-positive cells, were observed, whereas in the non-improved cases, cell-cell interactions were sparse. Instead, a dense infiltration of CD8-positive cells and CD3 and CD4-positive cells was observed in non-improved cases. Conclusion: Elucidation of the immune microenvironment of halo nevus is also relevant to melanoma-associated vitiligo and will contribute to our understanding of tumor immunity. Highlights: We collected 54 halo nevus patients and performed multivariate analysis and immunohistochemical analysis. The presence or absence of vitiligo vulgaris was associated with improvement in the surrounding vitiligo. Expression of PD-L1 in nevus cells was significantly higher in non-improved cases compared with improved case. Multiplexed immune cell phenotyping and spatial single-cell analyses of representative 2 cases were performe.